FREQUENCY OF METABOLIC SYNDROME IN PATIENTS PRESENTING WITH CHRONIC OBSTRUCTIVE PULMONARY DISEASE (COPD) AT DHQ TEACHING HOSPITAL RAWALPINDI (The Research of Medical Science Review, 2025)
Background: Chronic Obstructive Pulmonary Disease (COPD) is a progressive respiratory disorder associated with significant morbidity and mortality worldwide. Metabolic syndrome, comprising obesity, hypertension, hyperglycemia, and dyslipidemia, is increasingly observed among COPD patients, exacerbating disease severity and complicating management. Understanding the association between metabolic syndrome and COPD is crucial for better clinical outcomes. Objectives: To determine the frequency of metabolic syndrome among COPD patients and analyze its association with demographic and clinical characteristics. Study Design & Setting: A cross-sectional study was conducted at Medicine DHQ Teaching Hospital Rawalpindi from December 2024 to May 2025. A total of 90 diagnosed COPD patients were enrolled using non-probability consecutive sampling. Methodology: Data were collected through structured questionnaires, including demographic and clinical variables. Metabolic syndrome was defined according to the criteria established by the National Cholesterol Education Program Adult Treatment Panel III (NCEP ATP III). Stratification was performed based on age, gender, BMI, duration of COPD, and hemoglobin levels to assess the association between variables. Chi-square tests were applied, with a p-value ≤ 0.05 considered statistically significant. Results: The mean age of patients was 62.5 ± 8.7 years, with a male predominance (64.4%). The frequency of metabolic syndrome in COPD patients was 35.6%. Statistically significant associations were found between metabolic syndrome and gender (p = 0.048), BMI (p = 0.036), duration of COPD (p = 0.041), and hemoglobin levels (p = 0.021). Age group differences were statistically insignificant (p = 0.789). Conclusion: Metabolic syndrome is common among COPD patients and shows significant associations with gender, BMI, disease duration, and hemoglobin levels. Early identification and management of metabolic syndrome can improve the prognosis and quality of life in COPD patients.